Risk factors for hamstring muscle strain injury in sport: a systematic review and meta-analysis - Freckleton, G.; Pizzari, T. (British Journal of Sports Medicine, 2013)
Hamstring muscle strain-type injuries are common in sports that involve sprinting, acceleration, deceleration, rapid change in direction and jumping. Occurring in both recreational and professional sports, these injuries can result in substantial time lost from sport and commonly recur.